Training on washing procedures and flower arrangement according to hospitality industry standards through community partnerships at SMKN 1 Nusa Penida - I Wayan Restu Suarmana; Ni Luh Gde Sari Dewi Astuti; Putu Eka Wirawan; A.A. Istri Putera Widiastiti; I Gusti Made Riko Hendrajana (Community Empowerment, 2023)
Nusa Penida has many interesting tourist attractions to visit. The development of Nusa Penida as a tourist attraction, of course, human resources (HR) need to be improved, especially in the hospitality sector. To improve human resource development, the hotel management DIV study program at the International Tourism and Business Institute held community service activities (assisted SMK), by providing some training in the hospitality sector such as washing procedures and flower arrangement. The florist activities carried out are flower arrangement, types of flowers, characteristics of flowers. Then on laundry training such as chemical introduction, filling out laundry forms, using washing machines. The results obtained from this service activity are an increase in the knowledge of teachers and students regarding washing procedures and flower arrangement at SMKN 1 Nusa Penida.